2014
DOI: 10.5901/ajis.2014.v3n6p187
|View full text |Cite
|
Sign up to set email alerts
|

Health Problems and Health Seeking Behaviour of Hospital Cleaners in a Tertiary Health Facility in South West Nigeria

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 23 publications
0
9
1
Order By: Relevance
“…The present study shows a 12-month LBP prevalence rate of 78.2% among the cleaning workers. This prevalence rate slightly exceeds the rate of 72% and 63% reported by, [13,14] respectively, among janitorial workers in tertiary health institutions in Nigeria. It is similar to the rate observed among peasant farmers in a rural community, also in north-eastern Nigeria [19] just as the street cleaning workers in this study and is also comparable to that of peasant farmers in south-eastern Nigeria.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…The present study shows a 12-month LBP prevalence rate of 78.2% among the cleaning workers. This prevalence rate slightly exceeds the rate of 72% and 63% reported by, [13,14] respectively, among janitorial workers in tertiary health institutions in Nigeria. It is similar to the rate observed among peasant farmers in a rural community, also in north-eastern Nigeria [19] just as the street cleaning workers in this study and is also comparable to that of peasant farmers in south-eastern Nigeria.…”
Section: Discussioncontrasting
confidence: 58%
“…LBP is one of the musculoskeletal conditions that has been extensively studied in several occupational groups such as farmers, hospital workers, drivers and janitorial workers. [10][11][12][13][14] A high prevalence rate of 72.4% and 67% has been reported among peasants' farmers in South-west and South-South Nigeria, respectively. [11,12] The prevalence rate among cleaners or janitorial workers was reported as 77.2% [14] in South-South Nigeria and 63.1% [13] in South-West Nigeria.…”
Section: Original Article Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the preferential use of private hospitals was consistently observed in a study [24] among people in a university community where it was reported that most of them patronized private health care services but this, was not similarly observed in the study done by Ilesanmi et al [25], where the respondents, who were hospital cleaners, mostly patronized the government hospitals followed by Chemist shops with a few utilizing the private health care services. In these cases, socioeconomic status and probably the level of education, may have contributed to the type of health care services that were preferentially utilized, with people in a higher socioeconomic class tending to use private health care services.…”
Section: Discussionmentioning
confidence: 92%
“…In numerous occupational categories, it is one of the musculoskeletal disorders that has been thoroughly investigated (5,6).The 2010 Global Burden of Disease (GBD) study estimated that LBP is among the top 10 diseases and injuries that account for disability-adjusted life years worldwide (7). The magnitude of LBP is varied from 46 to 77% in different parts of the world(8-12).…”
Section: Introductionmentioning
confidence: 99%